Dinamika Islam Indonesia: Islam dan Politik di Indonesia - Surpani Surpani (Dialektika Publik, 2023)
Islam as the majority religion of Indonesian society has experienced development from time to time. In 2024 a General Election will be held to determine the President of Indonesia for the next five years. The aim of this article is to review the dynamics and development of Islamic politics in Indonesia. The research method is descriptive qualitative with secondary data sources, namely relevant research from journals and books as well as data documentation that strengthens this article. The data analysis technique uses triangulation techniques. The results of the article show that the opposition party uses this motive to fight party control. On the other hand, the incumbent party collaborates with Ulama from the largest Islamic organization in Indonesia. Media wars, arguments, and even insults are very easily thrown out by two parties competing to win the election, ironically the use of the words "party of Satan and party of God" was thrown out by a well-respected figure. Indonesia is not a religious country. Meanwhile, the relationship between religion and the state in Indonesia can be seen from religious institutions, laws and regulations related to religion or religious life, and other policies related to religious life.